Understanding the Pathogenesis of Xenobiotic-Induced Oxidative Stress in the Cardiac Microenvironment - Thomas S. H.; Gipson N.; Vaughn J.; Omeler C.; Dawkins N. L.; Bradford C. N. (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
The heart functions to ensure optimal perfusion of every organ while maintaining elasticity and compliance. Maintenance of cardiac output to ensure adequate perfusion of the heart itself and every organ in the body is the ultimate function of the heart. Mainly composed of cardiac myocytes, fibroblasts, endothelial and vascular cells, the heart has the highest energy demand of all organs. Thus, it requires a high rate of adenosine triphosphate (ATP) production to maintain normal physiological function. Using oxidative phosphorylation, the heart produces ATP and concomitantly produces reactive oxidative species (ROS). Therefore, normal homeostasis and mitochondrial metabolism make the heart extremely susceptible to intrinsic and extrinsic oxidative stress. Exogenous foreign agents or aberrantly expressed endogenous molecules are characterized as cardiac xenobiotics (CX) which promote cardiac-specific toxicity. CX enters the body via nutritional and drug intake or environmental exposure and causes an imbalance in ROS production and antioxidant protection within the cardiac microenvironment. The inhalation of toxic particles extends its damage to cardiovascular tissue promoting cardiac arrhythmia, altering cardiac repolarization, and increasing blood pressure. Chronic ROS exposure alters the cellular and molecular physiology of key detoxifying enzymes that modify cardiovascular structure and function. The heart has a tightly controlled antioxidant system that manages ROS and maintains homeostasis within the cardiac microenvironment. This strictly regulated system consists of endogenous enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) and exogenous antioxidants such as vitamins, minerals, polyphenols and carotenoids derived from nutritional sources. Sustained levels of cardiac xenobiotics can result in chronically imbalanced ROS production that outpaces the antioxidant system. Over time this imbalanced system results in irreversible cellular and subcellular damage, altering cardiac structure and function and increasing the risk of cardiac dysfunctions such as maladaptive left ventricular hypertrophy, cardiac fibrosis, and heart failure. Thus, it remains essential to clearly characterize the endogenous and exogenous antioxidants responsible for managing cardiac oxidative stress; determine the role of dietary intervention on ROS production; and provide alternative strategies for maintaining optimal protection against CX-induced oxidative stress.